Diseño de un centro de acopio, producción y capacitación agrícola para la parroquia “La Esperanza” del cantón Ibarra - Mugmal Iles, Claudio Jefferson (2024)
The parish of Santa Maria de la Esperanza is a place full of scenic wonders and ancestral knowledge of the indigenous culture inhabited by the Karan-qui indigenous population, it is located south of the city of Ibarra and shares neighboring territory with the parish of Angochahua. The parish is known for its hard-working and friendly people whose communication is based on two languages, Spanish and Kichwa or also called Quichua, the population stands out in agriculture with the diver-sity of cereals, vegetables, fruits and especially known as the tender and dry grains which is the live-lihood of most of the population, followed by gastronomy, folkloric music, clothing and ancestral knowledge. The population of the parish for a long time was and is recognized for its agricultural products, in which there has been a problem for decades of not having spaces or places where they can offer and sell their natural products such as cereals, vegetables, fruits and especially grains, causing the departure or emigration of the people of the sector to various jobs unrelated to their an-cestral knowledge, causing damage to their productive identity and customs in the future. There-fore, it is necessary to promote and strengthen the agricultural activity of the sector to generate so-cial and economic sustenance for the population and their families. We propose the design of a col-lection, production and agricultural training center in the parish of Santa Maria de la Esperanza in the canton of Ibarra belonging to the province of Imbabura, with the purpose of encouraging the in-habitants of the sector to take advantage of agriculture generating economy within the parish, this will help to avoid intentions of leaving their ancestral lands as well as being de-valued for their ef-fort and work in the economic aspect during the process of buying and selling.